2010
DOI: 10.1007/s00464-010-1186-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distractions in the operating room during endourological procedures

Abstract: BackgroundProfessionals working in the operating room (OR) are subject to various distractions that can be detrimental to their task performance and the quality of their work. This study aimed to quantify the frequency, nature, and effect on performance of (potentially) distracting events occurring during endourological procedures and additionally explored urologists’ and residents’ perspectives on experienced ill effects due to distracting factors.MethodsFirst, observational data were collected prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 18 publications
3
76
0
3
Order By: Relevance
“…This could be realized by the incorporating this as a mandatory item in a preoperative checklist [5,31]. Previous research has demonstrated that surgical flow disturbances are directly related to surgical performance [25,32,33]. The number of surgical flow disturbances per procedure that we objectified was in line with similar studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This could be realized by the incorporating this as a mandatory item in a preoperative checklist [5,31]. Previous research has demonstrated that surgical flow disturbances are directly related to surgical performance [25,32,33]. The number of surgical flow disturbances per procedure that we objectified was in line with similar studies.…”
Section: Discussionsupporting
confidence: 73%
“…Studies describing surgical processes were generally based on live observation in the OR; video observation has only been used infrequently [6,8,22,23]. Nevertheless, video registration is deemed superior since it is not limited by the capacity of an observer, cause-and-effect relationships are better analyzable, and the Hawthorne effect (i.e., the awareness of being observed alters the way a person behaves) is minimized [6,7,24,25].…”
mentioning
confidence: 99%
“…Periera et al (2011) "Distraction was defined as the behavior observed when there was diversion of attention during the execution of a primary task and/or a verbal response to a secondary task related or not related to the activity performed." Persoon et al (2011) "An interruption was defined as when a distraction leads to a break in main task activity." "A distracting stimulus was defined as any event that can cause diversion from the task at hand, and a distraction was any observed behavior indicating orientation away from the main task."…”
Section: Citationmentioning
confidence: 99%
“…Distracting events are common in the operating room, ranging from problems with equipment and unexpected procedure-related events to irrelevant conversations and interruptions. Residents and medical students are noted to be most negatively affected by distractions, whereas experienced surgeons were much more adept at multitasking and able to maintain a high level of proficiency despite distractions or interruptions [22,23]. Similarly, exposure to music or conversation as well as irritation with coworkers produces a decrease in surgical task performance by medical interns [24].…”
Section: Multitasking Distraction and The Doctor’s Performancementioning
confidence: 99%